Framework for developing an exposure science curriculum as part of the European Exposure Science Strategy 2020-2030 - Connolly, Alison (2022)
Background: Evaluating and managing exposures to chemical, physical, and biological stressors, which frequently interplay with psychological stressors as well as social and behavioural aspects, is crucial for protecting human and environmental health and transitioning towards a sustainable future. Advances in our understanding of exposure rely on input from well-trained exposure scientists. However, no education programmes in Europe are currently explicitly dedicated to covering the broader range of exposure science approaches, applications, stressors, and receptors. Objective: To address this challenge, a curriculum is needed that yields credible, well-defined career pathways in exposure science. Methods: Needs and conditions for advancing exposure to science education in Europe were identified. As a starting point for a way forward, harmonised learning outcomes for exposure science were defined at each level of the European Qualifications Framework. The course programme coordinators were recruited for three varying courses, with respect to the course level and the proportion of the curriculum dedicated to exposure science. These courses were assessed via our systematic course review procedure. Finally, strategic objectives and actions are proposed to build exposure science education programmes. Results: The ISES Europe ‘Education, Training and Communication’ expert working group developed a framework for creating a viable exposure science curriculum. Harmonised learning outcomes were structured under eight learning levels, categorised by knowledge, skills, and competence. Illustrative case studies demonstrated how education providers integrated these learning outcomes for their educational context and aligned the overall exposure science curriculum. Conclusions: The international recognition and adoption of exposure science education will enable advances in addressing global exposure science challenges for various stressors, from behavioural aspects from individual to population scale, and effective communication between exposure scientists and relevant stakeholders and policymakers, as part of the European Exposure Science Strategy 2020–2030.